2017
DOI: 10.7554/elife.29061
|View full text |Cite
|
Sign up to set email alerts
|

Centriole triplet microtubules are required for stable centriole formation and inheritance in human cells

Abstract: Centrioles are composed of long-lived microtubules arranged in nine triplets. However, the contribution of triplet microtubules to mammalian centriole formation and stability is unknown. Little is known of the mechanism of triplet microtubule formation, but experiments in unicellular eukaryotes indicate that delta-tubulin and epsilon-tubulin, two less-studied tubulin family members, are required. Here, we report that centrioles in delta-tubulin and epsilon-tubulin null mutant human cells lack triplet microtubu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 47 publications
(59 reference statements)
4
56
0
Order By: Relevance
“…Mutations in the Chlamydomonas ortholog of Tubd1 , encoded by the UNI3 gene, cause defects in the assembly of flagella, which are analogous to vertebrate motile cilia ( Dutcher and Trabuco, 1998 ). Centrioles in human cells lacking TUBD1 are unstable and fail to undergo maturation ( Wang et al., 2017 ). GLI1 induction was abolished in Tubd1 −/− NIH/3T3 cells ( Figures 4 B and S3 E) because nearly 100% of these cells lacked primary cilia ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in the Chlamydomonas ortholog of Tubd1 , encoded by the UNI3 gene, cause defects in the assembly of flagella, which are analogous to vertebrate motile cilia ( Dutcher and Trabuco, 1998 ). Centrioles in human cells lacking TUBD1 are unstable and fail to undergo maturation ( Wang et al., 2017 ). GLI1 induction was abolished in Tubd1 −/− NIH/3T3 cells ( Figures 4 B and S3 E) because nearly 100% of these cells lacked primary cilia ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…Of the many characterized isoforms within the tubulin protein superfamily, the delta and epsilon tubulin variants remain incompletely understood. Recent work has suggested that these isoforms exist as an evolutionarily conserved module (Turk et al, 2015) and may be involved in forming triplet microtubules that are critical for centriole assembly (Wang et al, 2017a). …”
Section: Resultsmentioning
confidence: 99%
“…as the A-and B-microtubule inner junction would be missing. As a consequence, the 421 inner scaffold proteins will not be recruited, as already shown for POC5, leading to the 422 observed futile cycle of centriole formation and disintegration (Wang et al, 2017). It 423 would therefore be interesting to study the presence of WDR90 in these null mutants 424 as well as the other components of the inner scaffold in the future.…”
Section: Wdr90 Depletion Leads To a Loss Of Inner Scaffold Componentsmentioning
confidence: 96%